The Efffect of Environmental Management Accounting, Environmental Strategy on Environmental Performance and Financial Performance Moderated By Managerial Commitment - Eko Cahyo Mayndarto; Yvonne Agustine (International Journal of Science, Technology & Management, 2021)
Environmental management (EMA) has been considered as a successful idea to reduce ecological burdens in the form of energy dependence and carbon footprint. In addition to the company's highest emphasis on EMA, the organization's environmental strategy (ENS) is articulated and implemented with ecological motivation. The role of the ENS strengthens the internal awareness of the organization to improve environmental conditions and thereby helps reduce negative environmental stresses. In addition, with increasing environmental regulations in place, the need for sound environmental policies and strategies of the company is essential to protect future growth and market image. Results There is a significant influence of environmental management accounting to encourage environmental performance, there is a significant effect of environmental management accounting to encourage economic performance, there is a significant influence of environmental strategy to encourage environmental performance, there is a significant influence of environmental strategy to encourage economic performance, commitment to moderate management The significant influence of Environmental Management Accounting to encourage Environmental Performance, Management Commitment Cannot Moderate the Effect of Environmental Management Accounting which encourages Economic Performance, Management Commitment to Moderate the significant influence of Environmental Strategy to encourage Environmental Performance and Management Commitment to Moderate the Impact of Environmental Strategy which is significant to encourage Economic Performance .